Study test environmental parameters terubuk fishing Areasln the waters of the strait bengkalis Bengkalis regency riau province - Muhd Hafiz; Alit Hindri Yani; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The Object from this observation is physical and chemical parameters fromTerubuk fishing areas of the Strait Bengkalis with literature studies . Thereasearch was conducted in August-November 2013. The method of this study is asurvey method in data physical and chemical parameters measured directly.While reasearch area of data obtained were Terubuk catches of fisheries andmarine Bengkalis regency . The data obtained were analysis deskriftiptively bystudy of the research literature describes the waters condition from streaitbengkalis is very supportive to the organisms live and feasible to do fishingactivities activities and terubuk aquaculture.Keywords : Terubuk Fish (Tenaulusa Macrura ) . Fishing Areas(fishing ground ) . Physical and Chemical Parameters of Waters . Strait Bengkalis.